Deep habits and the macroeconomic effects of government debt - Rym Aloui (Deutsche Bundesbank, 2010)
In this paper, we study the effects of government debt on macroeconomic aggregates in a non-Ricardian framework. We develop a micro-founded framework which combines time-varying markups, endogenous labor supply and overlapping generations based on infinitely-lived families. The main contribution of this paper is to provide a new transmission mechanism of public debt through the countercyclical markup movements induced by external deep habits. We analyze the effects of debt-financed tax cuts. We show that the interest rate rises, entailing higher markups, which imply a fall in employment and consumption. It is particularily noteworthy that, even without capital, a crowding out effect of government debt is obtained in the long run. However, the short-run expansionary effect of debt-financed tax cuts, which would eventually be expected in a non-Ricardian framework, fails to occur. This is due to our flexible-price framework. On the other hand, we show that incorporating sticky prices in our model causes debt-financed tax cuts to have a short-run expansionary effect while preserving the long-run contractionary effect.
Keywords: E63; E52; 330; Wealth Effects; Fiscal Policy; Public Debt Shock; Deep Habits; Overlapping Generations; Monopolistic Competition; Öffentliche Schulden; Makroökonomischer Einfluss; Crowding out; Steuerpolitik; Vermögenseffekt; Overlapping Generations; Monopolistischer Wettbewerb; Theorie